O mundo do trabalho e a qualificação profissional: análise das egressas do Programa Mulheres Mil, do Instituto Federal de Goiás (IFG) – Campus Itumbiara - Ponciano, Roberta Rodrigues (2017)
This research aims to identify and analyze how occurred the insertion of the egresses in the world of work, according to the training obtained in the courses offered in Thousand Women Program, developed at Instituto Federal de Goiás (IFG) – Itumbiara Campus. Women who took the course in the period from 2012 to 2014 were the object of the study, portraying how the egresses of the first classes are today and those who attended it after the insertion of Thousand Women in Pronatec/Brazil without Misery. Thousand Women Program is a public policy of professional qualification, in order to allow the exclusively access of women in a poverty situation and social vulnerability to professional and technological education, in an attempt to increase the access and mobility opportunities in the labor market. It should be noted that women‟s work presents a historicity publicized in governmental discourses through public policies, as a pressure for changes in the historical exclusion of women from the labor market. Meanwhile, Thousand Women Program is a professional qualification with contradictions throughout its development: theoretically, it indicates an education that would seek the totality of the learning, but in practice, it was not able to perform that accomplishment. The results show that Thousand Women Program centers only on the idea of professionalizing education, with a rapid and unsatisfactory training of female labor force in diverse contexts that include precariousness, informality, unemployment, flexible, housekeeping etc. Thus, in terms of education and work, the courses limited the access to citizenship and the equity of these women, with naturalization of the gender differences and the maintenance of the students in vulnerable situations, in relation to the labor market. In fact, these courses provided extensive knowledge focused on jobs with feminine characteristics that frequently refer to precarious activities that reinforced the inequalities experimented by them.